RND1 inhibits epithelial-mesenchymal transition and temozolomide resistance of glioblastoma via AKT/GSK3-β pathway - Qian Sun; Junjie Xu; Fan’en Yuan; Yan Liu; Qianxue Chen; Lirui Guo; Huimin Dong; Baohui Liu (Cancer Biology & Therapy)
GBM is one of the most malignant tumor in central nervous system. The resistance to temozolomide (TMZ) is inevitable in GBM and the characterization of TMZ resistance seriously hinders clinical treatment. It is worthwhile exploring the underlying mechanism of aggressive invasion and TMZ resistance in GBM treatment. Bioinformatic analysis was used to analyze the association between RND1 and a series of EMT-related genes. Colony formation assay and cell viability assay were used to assess the growth of U87 and U251 cells. The cell invasion status was evaluated based on transwell and wound-healing assays. Western blot was used to detect the protein expression in GBM cells. Treatment targeted RND1 combined with TMZ therapy was conducted in nude mice to evaluate the potential application of RND1 as a clinical target for GBM. The overexpression of RND1 suppressed the progression and migration of U87 and U251 cells. RND1 knockdown facilitated the growth and invasion of GBM cells. RND1 regulated the EMT of GBM cells via inhibiting the phosphorylation of AKT and GSK3-β. The promoted effects of RND1 on TMZ sensitivity was identified both in vitro and in vivo. This research demonstrated that the overexpression of RND1 suppressed the migration and EMT status by downregulating AKT/GSK3-β pathway in GBM. RND1 enhanced the TMZ sensitivity of GBM cells both in vitro and in vivo. Our findings may contribute to the targeted therapy for GBM and the understanding of mechanisms of TMZ resistance in GBM.